2017
DOI: 10.18203/2349-2902.isj20173208
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinical and pathological correlation of benign breast lesions

Abstract: Background: Benign breast diseases are common in females among young age group. Most common presentation is painless lump in the breast. Clinical and pathological correlation is essential. Fibroadenoma is the commonest among all other benign breast diseases. The aim was to study the age distribution of benign breast diseases. To study different types of benign breast diseases, their mode of clinical presentation and to correlate with radiological examination, cytology and histopathology of breast diseases.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 8 publications
4
15
0
Order By: Relevance
“…Ramesh et al stated that 24% of had lumps associated with pain. 36 Chalya et al indicated that most of the patients (67.8%) of had breast nodularity associated with pain. 37 Mastalgiais highly seen in third decades of women life.…”
Section: Discussionmentioning
confidence: 99%
“…Ramesh et al stated that 24% of had lumps associated with pain. 36 Chalya et al indicated that most of the patients (67.8%) of had breast nodularity associated with pain. 37 Mastalgiais highly seen in third decades of women life.…”
Section: Discussionmentioning
confidence: 99%
“…Benign breast diseases are heterogeneous group of lesions with diverse symptoms and or detected by incidental microscopic findings. 1 30% of the women suffer from benign breast diseases and require treatment. 2 The lesions are common in younger population, the incidence rises during the second decade and peak in the fourth and fifth decades.…”
Section: Introductionmentioning
confidence: 99%
“…Benign breast disease is usually common in younger population and the incidence rises during the second decade of life and peaks in the fourth and the fifth decade. (2) Currently the female breast is one of the most commonly biopsied tissue because of myriads of diseases and lesions that arise from it. (3) Benign breast diseases forms majority, accounting for 90% of breast lesions worldwide.…”
mentioning
confidence: 99%
“…Treatment of benign breast diseases is preservation of breast tissue as far as possible in contrast to traumatizing mutilating surgeries in breast cancer. (2) In other words, in order to prevent unnecessary loss of breast, accurate diagnosis of non malignant lesions is of utmost importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation